2015
DOI: 10.1017/neu.2015.46
|View full text |Cite
|
Sign up to set email alerts
|

Fluid intelligence and executive functioning more alike than different?

Abstract: Gf and EF are highly correlated. Gf dysfunction in neuropsychiatric patients warrants further EF examination and vice versa. It is discussed that results confirm the need to distinguish between specific versus general fluid/executive functioning, the latter being more involved when task complexity and novelty increase. This distinction can provide a more refined differential diagnosis and improve neuropsychiatric treatment indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…Although intelligence and executive functions are distinct constructs, aspects of intelligence, such as fluid intelligence, are highly correlated with executive functioning, and impairments in both constructs result from injury to the same brain regions. 96 As a result, some authors fail to distinguish higher-level executive functions from fluid intelligence. 96 In the present study, the lack of mediation in the moderate TBI group likely reflects the more limited effects of such injuries on neuropsychological skills and adaptive functioning, producing relatively weak associations between these domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although intelligence and executive functions are distinct constructs, aspects of intelligence, such as fluid intelligence, are highly correlated with executive functioning, and impairments in both constructs result from injury to the same brain regions. 96 As a result, some authors fail to distinguish higher-level executive functions from fluid intelligence. 96 In the present study, the lack of mediation in the moderate TBI group likely reflects the more limited effects of such injuries on neuropsychological skills and adaptive functioning, producing relatively weak associations between these domains.…”
Section: Discussionmentioning
confidence: 99%
“…96 As a result, some authors fail to distinguish higher-level executive functions from fluid intelligence. 96 In the present study, the lack of mediation in the moderate TBI group likely reflects the more limited effects of such injuries on neuropsychological skills and adaptive functioning, producing relatively weak associations between these domains. In support of this possibility, studies of typically developing children have also found weak associations between cognitive measures and adaptive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have tried to unify intelligence and neuropsychological assessment based on the CHC model [58,[63][64][65][66][67][68][69][70][71]. For example, Jewsbury et al [65] showed that popular neuropsychological EF tests were subsumable under CHC broad cognitive abilities based on factor analytic methods, although particular EF tests were related to distinct CHC constructs.…”
Section: Introductionmentioning
confidence: 99%
“…). Furthermore, factor analytic studies have demonstrated that the Matrix Reasoning subtest loads with other tests of executive functions, such as the WCST and the Stroop test (van Aken, Kessels, Wingbermühle, van der Veld,& Egger, 2016;van Aken et al, 2014). In an adult sample, the split-half reliability of the…”
mentioning
confidence: 99%